(3QSGdI eTGYQs - (3GdTjQGRj, GdbhGej, GdeqdG, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1059 (3g`s ((3MQGfs)
(3ChdgG (B:s
(3fMeO Gddg hfSJYjf HbhJg GdJj CbGe HgG edchJ GdCQV hGdSeGA CjgG GdENhGf GdSGdchf Edi Gddg HfhQ GdYQaGf(B! (3GSJeYhG HGSJeGY bdhHce ebGdJj djfaP aj HhGWfce fhQ MceJj s
(3BNQgG (B:s
... (3Ke jYQL Edjg HJchjf GdLeGO ef JYOjd GdYfGUQ hGdCQcGf Ke GdfHGJ ef UahgG Ke GdMjhGf Ke GdEfSGf hEPG GSJced HGdYde hGdceGd HdZ OQLI GdYbd GdaYGd ajg hba JQJjH GdNjQ hGdLhO (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\303s
(3EjVGM Gdecfhf (B2\332s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs